Representativeness and climatology of carbon monoxide and ozone at the global GAW station Mt. Kenya in equatorial Africa - (:unkn) unknown (My University, 2007)
The tropics strongly influence the global atmospheric chemistry budget. However, continuous in-situ observations of trace gases are rare especially in equatorial Africa. The WMO Global Atmosphere Watch programme aimed to close this gap with the installation of the Mt. Kenya baseline station. Here, the first continuous measurements of carbon monoxide (CO) and ozone O3 at this site are presented. The representativeness of the site was investigated by means of statistical data analysis, air mass trajectory clustering, interpretation of biomass burning variability and evaluation of O3-CO relationships. Despite its location in equatorial Africa the site was rarely directly influenced by biomass burning emissions, making it suitable for background observations. Located at 3678 m above sea level the night-time (21:00?04:00 UTC) measurements were in general representative of the free troposphere, while day-time measurements were influenced by atmospheric boundary layer air. Six representative flow regimes towards Mt. Kenya were determined: eastern Africa (21% of the time), Arabian Peninsula and Pakistan (16%), northern Africa free tropospheric (6%), northern Indian Ocean and India (17%), south-eastern Africa (18%) and southern India Ocean (21%). The seasonal alternation of these flow regimes was determined by the monsoon circulation and caused a distinct semi-annual cycle of CO with maxima during February and August and with minima in April and less pronounced in November. O3 showed a weaker annual cycle with a minimum in November and a broad summer maximum. Inter-annual variations were explained with variations in southern African biomass burning and in transport patterns. The measurements at MKN were representative of air masses with little photochemical activity as indicated by weak O3-CO correlations, u
Keywords: African Research